PEMBINAAN MENTAL DALAM UPAYA PENINGKATAN PERILAKU KEBERAGAMAAN (STUDI PADA RUMAH TAHANAN NEGARA KLAS IIA PONDOK BAMBU) - Hadi Wibowo (Yayasan Akrab Pekanbaru, 2019)
Mental development activities conducted at Pondok Bambu Class IIA Pondok Bambu East Jakarta include spiritual activities such as pengajian. The regular recitation schedule which is held every Monday, Tuesday, Wednesday and Thursday, Friday is held in the mosque and library room. As instructors in the spiritual activities / recitations came from the Prisoner Staff assisted by the Islamic Religion Extension Staff of the Ministry of Religion, East Jakarta, some were from foundations or from other religious organizations. For the material given, namely in the form of spiritual shower / tausiah, learning to read iqro / Al-Qur'an, and other religious material such as tauhid, fiqh, morality and various other activities such as activities in the month of Ramadan, maulid prophet and Islamic holidays. In the implementation of mental development / spiritual activities, the routines carried out every day are only followed by some of the residents assisted by the number of assistants who are available. It is indeed very unfortunate, so large is the number of prisoners but only a few who follow it.